The Political Spectacle of the Humanitarian Agreement and Hugo Chavez's Mediation during the Second Administration of Álvaro Uribe - Constain, Manolo; Rouvinski, Vladimir (My University, 2012)
During Álvaro Uribe’s second term in power, diplomatic relations between Colombia and Venezuela were marked by severe difﬁculties that triggered several crises. With the arrival of Juan Manuel Santos to power, however, these difﬁculties seem to have been resolved unexpectedly fast. Hence, rather than being a crisis caused by some structural aspects of bilateral relations, the dispute was about misunderstandings and tensions that can be linked to speciﬁc dynamics of the relationship between Hugo Chávez and Álvaro Uribe. The authors use the concept of political spectacle proposed by Edelman (1988) in order to examine the relationship in question. From this perspective, the unsuccessful attempt to reach a humanitarian agreement with the mediation of Hugo Chávez that took place during the second half of 2007 can be considered as the ﬁrst relevant event to analyze in the Venezuelan and Colombian leaders’ conﬂictive interactions at the time. The article examines the way in which the political developments of this period were interpreted and transmitted by the El Tiempo newspaper immersed in a political spectacle that was based on a government-media relationship and aimed at generating support of the government in the public opinion through the symbolic use of the kidnapping issue.

Durante el segundo mandato de Álvaro Uribe Vélez, los presidentes de Colombia y Venezuela entraron en un período de desencuentro que generó grandes ﬁsuras en sus relaciones diplomáticas y desencadenó distintas crisis. Con la llegada de Juan Manuel Santos a la Presidencia de Colombia, el conﬂicto parece haberse resuelto de una forma inesperadamente rápida. Lo anterior supone que, más que una crisis colombo-venezolana basada exclusivamente en aspectos estructurales de la relación, los desencuentros y tensiones del período especiﬁcado responden a dinámicas propias de la relación entre Álvaro Uribe y Hugo Chávez. El concepto del espectáculo político propuesto por Edelman (1988) permite abordar el análisis de las relaciones entre estos mandatarios desde una perspectiva poco utilizada en la literatura latinoamericana. El fallido acuerdo humanitario y la mediación de Hugo Chávez en la segunda mitad de 2007 se pueden considerar como la primera coyuntura relevante por analizar desde este concepto en la trayectoria de conﬂicto que experimentaron ambos presidentes en ese entonces. El artículo analiza la forma en la cual los desarrollos políticos de este período fueron interpretados y transmitidos por el periódico El Tiempo de un modo determinado, como parte de un espectáculo político que, apoyado en la relación gobierno-medios, estaba encaminado a generar apoyo político en la opinión pública, a través del uso simbólico del tema del secuestro.
El espectáculo político del acuerdo humanitario y la mediación de Hugo Chávez durante el segundo mandato de Álvaro Uribe
Keywords: Ciencia política; Political science; Acuerdo humanitario; Foreign policy; Espectáculo político; Political spectacle; Política exterior; Symbols; Símbolos; Humanitarian agreement; Medios de comunicación; Mass media